(untitled) (Research, Society and Development, 2023)
There is some controversy about the safety of invasive dental treatments in patients on bisphosphonates. The objective of this research was to verify, through the application of a questionnaire, the degree of knowledge that specialist physicians in Geriatrics, Rheumatology, Orthopedics, Gynecology and Oncology have about the interrelationship between the use of bisphosphonates and their effect on the bones of the maxilla and mandible. 100 health professionals were selected, uniformly distributed in five specialties. All were submitted to a questionnaire and the answers were tabulated. The highest indication of bisphosphonates was for osteoporosis 94%, followed by bone metastasis, Paget’s disease, hypercalcemia, lytic lesion and bone fracture. As for the class of bisphosphonates, 50% of gynecologists, 78% of orthopedists, 94% of geriatricians and 100% of oncologists and rheumatologists answered that they prescribe the nitrogen class. Regarding the route of administration, geriatricians, gynecologists, orthopedists and rheumatologists prefer the oral route and only oncologists reported a preference for the parenteral route. The risk of osteonecrosis of the jaw related to the use of bisphosphonates is accepted by most physicians interviewed. All respondents refer all patients who have complications in the oral cavity resulting from the use of bisphosphonates to the dentist, however, they still do not indicate regular visits to the dentist before the onset of complications. We consider that there should be greater communication between the doctor and the dentist in cases where the patient uses bisphosphonates before and during treatment to minimize the severity of injuries involving the maxilla and mandible bones.